Challenging Gender Norms: Male Physicians' Perspectives on Family Planning in Rural Islamabad - Junaid Jamshed; Rida Shakil; Muhammad Hassan Laique (Journal of University College of Medicine and Dentistry)
Objective: To explore male physicians' perceptions of how family planning (FP) training, supportive supervision, and access to educational materials impact their knowledge, confidence, and ability to provide FP services in rural areas of Islamabad, Pakistan, where FP is traditionally considered a female domain.